The in-betweens of lifeworlds: Double clicks of becoming-entrepreneurial - Amin, Ahmed (AUC Knowledge Fountain, 2018)
In this project, I de-naturalize dynamics of the establishment of social entrepreneurship as a political project that has on the underside of it after-modern passions and desires with an affinity to the European Renaissance and the West as, according to Michel-Rolph Trouillot, “a project not a place, a multi-layered enterprise in transparent universality” (Trouillot, 1991: 32). I purse de-naturalization through de-scription. I de-scribe and trace relationships and inter-actions that are made and re-made in the name of social entrepreneurship. In those very inter-actions, entrepreneurial bodies are re-assembled. According to Gilles Deleuze and Félix Guattari (1987), “we know nothing about a body until we know what it can do” (p. 257). Hence the emphasis on actions. As such, the political becomes a mode of organization and distribution of solutions that entrepreneurs assemble around contesting and conflicting needs, wants and desires. Often-times, those needs, wants and desires are made visible through acts of making and re-making of containers, such as the Social Entrepreneur and the Bedouin. I do not understand those containers as actors, but actants. According to Bruno Latour (2005), actants is the activity of translation and mediation of actions. Those actions take place in the milieu of the after-modern. That milieu is a continuum that exists in mesh of different lifeworlds. Hence, there is no singular contemporary that prevails and dominates. Each lifeworld has its own contemporary, make and is made by other lifeworlds. In that sense, markets are not only the way ahead; life unfolds as one acts; there are no linear movements. I focus on processes and multiplicities of actions that make and re-make the contemporary whenever it is experienced. I in-turn do not trace the what, but the how. In specific, how individuals enter and exit market relationships through acts of setting prices of products and engaging in activities to acquire a formal status of their businesses. In those very processes, intimacies of life such as family, home and security acquire and grant meanings not only to actors, but to actions. I trace those actions through focusing on moments of, according to Bruno Latour (2013), double click. It is a moment when power materializers to re-configure socialites and life itself. In this project, I am using double click as a method in order to trace changing modes of existence. It is a method that I use to de-scribe relational traces that are in-action. By socialities, I mean relationships that are being made and remade in the name of social entrepreneurship.